PERILAKU BAHASA MENYIMPANG PESERTA DIDIK - Kusmana, Ade (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
Abstrak:Language is one of the parameters in young learners’ development. The ability in speech and language involve cognitive, sensorimotor, psychological, emotional and environmental developments around the children. When the principles of coordination between the mind and physiological mechanism is not working properly, language deviation will happen. The main categories of language deviation in relation to home environment are: (1) as a part of the normal development of children’s language, and (2) as a result of psychogenic or physiogenic disorders. Language behavior deviation becomes significant in the lives of school children. All forms of disorders of speech and all levels of disorder will not be separated from the classroom so the disorder problem should not be involved in the classroom situation. Abstrak: Bahasa merupakan salah satu parameter dalam perkembangan anak. Kemampuan berbicara dan berbahasa melibatkan perkembangan kognitif, sensorimotor, psikologis, emosi, dan lingkungan sekitar anak. Ketika prinsip-prinsip koordinasi antara akal pikiran dan mekanisme fisiologis tidak berfungsi secara sempurna maka terjadilah penyimpangan bahasa. Kategori utama penyimpangan bahasa dalam hubungannya dengan lingkungan rumah adalah (1) yang terbentuk sebagai bagian dari perkembangan normal bahasa anak, dan (2) sebagai akibat dari gangguan psychogenic atau physiogenic. Perilaku bahasa menyimpang menjadi signifikan dalam kehidupan sekolah anak-anak. Segala bentuk kelainan berbicara dan seluruh tingkat kelainannya tidak akan terpisahkan dari kelas. Sehingga masalah kelainan semestinya tidak terlibat dalam situasi kelas.